Видовой состав Cyanoprokaryota планктона Чебоксарского водохранилища (Нижегородская обл., Россия) - Охапкин, А.Г.; Воденеева, Е.Л.; Бондарев, О.О. (Альгология, 2015)
Проведена ревизия состава синезеленых водорослей (Cyanoprokaryota, Cyanophyta) Чебоксарского водохранилища с учетом современных данных о систематике и номенклатуре таксонов. Установлено 73 вида из 27 родов, 9 семейств и 3 порядка. According to the recent data on the taxonomy and nomenclature of taxa a revision of blue-green algae composition (Cyanoprokaryota, Cyanophyta) of Cheboksary reservoir was conducted. It was found 73 species from 27 genera, 9 families and 3 orders. The main part of the Cyanoprokaryota flora was formed by representatives of genera Dolichospermum, Merismopedia, Chroococcus, Microcystis, Rhabdogloea, Oscillatoria. Taxonomic, ecological and geographical characteristics of blue-green algae were given. Main changes in the taxonomic structure of this group of algae after the Volga River flow regulation were marked. The most important of them were the increasing of total species richness of Cyanophyta, the appearance of new species of five genera and the increasing diversity of the genus Dolichospermum nearly twice.